MOSPD2 is a therapeutic target for the treatment of CNS inflammation. (18th May 2020) - Yacov, N.; Kafri, P.; Salem, Y.; Propheta‐Meiran, O.; Feldman, B.; Breitbart, E.; Mendel, I.
Summary: In multiple sclerosis and experimental autoimmune encephalomyelitis (EAE), myeloid cells comprise a major part of the inflammatory infiltrate in the central nervous system (CNS). We previously described that motile sperm domain‐containing protein 2 (MOSPD2) is expressed on human myeloid cells and regulates monocyte migration in vitro . The role of MOSPD2 in EAE pathogenesis was studied by generating MOSPD2 knock‐out (KO) mice and monoclonal antibodies directed against MOSPD2. We found that EAE development in MOSPD2 KO mice was significantly suppressed. While frequency representation of leukocyte subsets in lymphoid tissues was comparable, the ratio of inflammatory monocytes in the blood was markedly reduced in MOSPD2 KO mice. In addition, T cells from MOSPD2 KO mice displayed reduced secretion of proinflammatory cytokines and increased production of interleukin (IL)‐4. Prophylactic and post‐onset treatment using monoclonal antibodies (mAbs) generated against MOSPD2 abrogated development and reduced EAE severity. These results suggest that MOSPD2 is key in regulating migration of inflammatory monocytes, and that anti‐MOSPD2 mAbs constitute a potential therapy for the treatment of CNS inflammatory diseases. Abstract : We explored the role of motile sperm domain‐containing protein 2 (MOSPD2), a newly characterized protein expressed by monocytes, in experimental autoimmune encephalomyelitis (EAE) pathogenesis. We show that EAE was significantly suppressed in MOSPD2 KO mice or after treatment of wild‐type mice with anti‐MOSPD2 monoclonal antibodies, with pathological evidence demonstrating restricted monocyte and T cell infiltration into the CNS. The study substantiates a key role for MOSPD2 in regulating migration of inflammatory monocytes and suggests that anti‐MOSPD2 antibodies constitute a potential therapy for the treatment of CNS inflammatory diseases such as multiple sclerosis via a mechanism that interferes with monocyte accumulation in the CNS.